Komunikasi Interpersonal Kyai dan Santri dalam Pesantren Modern di Tasikmalaya, Sebuah Pendekatan Interactional View - Nadia Wasta Utami (Jurnal Komunikasi)
Kyai-santri in a system called pesantren, has a unique relationship which is formed from the process of continuous interaction in teaching-learning process and in daily life. In this relation, kyai and santri generally keep using interpersonal communication as the main choice in interaction. This paper aims to explore the interpersonal communication between kyai and santri in modern pesantren in Tasikmalaya by using Watzlawick's interactional view approach. The method used is qualitative descriptive with data retrieval technique namely literature study, observation and interview. The research found that, kyai and santri cannot not do communication: both verbal and non verbal; both kyai and santri not only communicate the content but also have a unique way of building relationships; message delivery type is symmetrical with dominated by kyai; and there are many unwritten communication rules of santri-kyai showing the santri's respect for their kyai.